Enhanced wooden polymer composites based on polyethylene and nano-modified wooden flour - Hamdy M. Naguib; Eman O. Taha; Mona A. Ahmed; Usama F. Kandil (Egyptian Journal of Petroleum)
Usage and functionalization of natural fiber in preparing “wooden-plastic composite (WPC)” is aimed, the research investigates the influence of treatment of “wooden flour” using “carbon nanotube (CNT)”, and applying U.V wreathing conditions on wooden flour-polyethylene (WF-PE) WPC. The novelty of this work is the dual functionalization of WF via hydrolysis and reaction with CNT, for better attachment with PE matrix. WF was firstly washed and then treated with CNT to obtain WWF and functionalized WWF-CNT, respectively. Proposed nanocomposites have been prepared using “extrusion” based on polyethylene filled with 50 wt% of wooden fillers (WF, WWF, WF-CNT and WWF-CNT). “Fourier transform infrared (FTIR)” charts and “transmission electron microscope (TEM)” photos indicated the reaction between functionalized CNT and treated fiber through esterification. The findings of “thermal gravimetric analysis (TGA)” indicate more residual ash and higher onset temperature for PE-WWF-CNT and PE-WF, respectively; the thermal stability of all WPCs was also increased after U.V exposure. Furthermore, “dynamic mechanical analysis (DMA)” shows significant improvement in modulus after treatment reaction, and changing in loss factor and thermal transitions. The WWF-CNT-containing WPC achieved higher moduli, even after U.V exposure, due to good interaction between PE matrix and CNT-functionalized fibers, which restricts the molecular mobility. The characterization sentence declares that composite filled with CNT-functionalized fibers is the most stable formula.